PELESTARIAN BAHASA, AKSARA, DAN SASTRA BALI MELALUI PENGOPTIMALAN TRIPUSAT PENDIDIKAN - I MADE ARIASA GIRI (Purwadita : Jurnal Agama dan Budaya, 2017)
The  existence  of  language,  akasara,  and  literature  Bali  has  a  position  and  a  very important  function,  namely  as  a  pillar  of  the  nation's  cultural  development.  Along  with  the development of  globalization, its  presence  is  experiencing  a dynamic, such as the  decrease  in the use of language Bali in quantity and quality. It is  increasingly threatening kelestraiannya, whereas language, literacy and regional literature has an important role in building character or  national  identity.  Therefore,  it  is  important  to  efforts  to  preserve  the  language,  script  and literature tripusat Bali through optimization of education, the family environment, school, and community. Family environment is an environment is first and foremost for a child. The school environment  is  a  second  environment  for  children  to  socialize  and  interact.  Community environment is also very important take on the role especially Pakraman and community leaders. In the preservation of language, literacy, and literary Bali can not be separated from a variety of challenges.